The Effects of Increased Midsole Bending Stiffness of Sport Shoes on Muscle-Tendon Unit Shortening and Shortening Velocity: a Randomised Crossover Trial in Recreational Male Runners - Cigoja, Sasa (Sports Med Open, 2020)
BACKGROUND: Individual compliances of the foot-shoe interface have been suggested to store and release elastic strain energy via ligamentous and tendinous structures or by increased midsole bending stiffness (MBS), compression stiffness, and resilience of running shoes. It is unknown, however, how these compliances interact with each other when the MBS of a running shoe is increased. The purpose of this study was to investigate how structures of the foot-shoe interface are influenced during running by changes to the MBS of sport shoes. METHODS: A randomised crossover trial was performed, where 13 male, recreational runners ran on an instrumented treadmill at 3.5 m·s(−1) while motion capture was used to estimate foot arch, plantar muscle-tendon unit (pMTU), and shank muscle-tendon unit (sMTU) behaviour in two conditions: (1) control shoe and (2) the same shoe with carbon fibre plates inserted to increase the MBS. RESULTS: Running in a shoe with increased MBS resulted in less deformation of the arch (mean ± SD; stiff, 7.26 ± 1.78°; control, 8.84 ± 2.87°; p ≤ 0.05), reduced pMTU shortening (stiff, 4.39 ± 1.59 mm; control, 6.46 ± 1.42 mm; p ≤ 0.01), and lower shortening velocities of the pMTU (stiff, − 0.21 ± 0.03 m·s(−1); control, − 0.30 ± 0.05 m·s(−1); p ≤ 0.01) and sMTU (stiff, − 0.35 ± 0.08 m·s(−1); control, − 0.45 ± 0.11 m·s(−1); p ≤ 0.001) compared to a control condition. The positive and net work performed at the arch and pMTU, and the net work at the sMTU were significantly lower in the stiff compared to the control condition. CONCLUSION: The findings of this study showed that if a compliance of the foot-shoe interface is altered during running (e.g. by increasing the MBS of a shoe), the mechanics of other structures change as well. This could potentially affect long-distance running performance.